The great Egyptian grave robbery - Pennypacker, Sara, 1951- (Flat Stanley's worldwide adventures, 2009)
Asked to travel to Egypt to help with an urgent archaeological expedition, Flat Stanley suspects that he might be helping grave robbers and must rely on his quick thinking, unique flatness, and new friends to make things right.